The Relationship between Employees and Organizations to Explore the Innovative Behavior for Sustainable Organizations - Yulianti, Praptini; Arina, Nidya Ayu (International Journal of Psychosocial Rehabilitation, 2020)
The human dimension is the key resource for maintaining organizational competitive advantage and sustainable development. This dimension is related to the processes of generating social health and enhancing employee well being, such as (organizational justice, employe’s work engagement, trust on leader, Innovative behavior) could be a key component of the human dimension of organizational sustainability. The objective of this study is to examine the influence of organizational procedural justice, work engagement, trust on leader on innovative behavior. Sample of this study is 120 employees in television media, on marketing division, technique, program, production, and news in Surabaya. These division have become sample because of the jobs inside that division demand innovation. Data collected with questionnaire and technique analyses using PLS. The result of this study is procedural justice significance influenced to work engagement and trust on leader. Trust on leader and work engagement are significantly influenced by innovative behavior. The implication of this study is organizations must create justice climate so employee perceives well being that they will explore innovative behavior as a human performance to generate organizational sustainability.